Environmental management model in coastal area (a case study of ecopesantren Al-Khairat Palu, Central Sulawesi). Issue 1 (May 2021) - Aulia, R N; Jasin, F M; Anggraeni, D; Narulita, S; Mardhiah, I; Hadiyanto, A
Abstract: This study aimed to determine the environmental management model in coastal areas based on ecosystems; Pesantren Al-Khairat in Central Sulawesi, Case Study. Optimizing environmental conservation is done through many factors, and religious elements become one of these factors; religion becomes a way to shape the character of its adherents in protecting their environment. Islam as a religion has teachings that direct its supporters to protect the environment adequately so that the instructions are in harmony with the concept of environmental conservation. This research uses ecopesantren theory with several indicators. First, the pesantren policy that carries out environmental management by utilizing land to create artificial forests. Utilization is based on an agroforestry, agrosilvopasteur and agrofishery approach. The zone of mangrove forest utilization can help food security and environmental preservation in the Pesantren environment. The existence of an artificial lake as a water catchment area supports efforts to conserve water in Pesantren. Also serves as a water reserve through rainwater collection so that it can minimize the occurrence of flooding. Second, participatory activity-based environmental development policies. Pesantren make santri as an aid team in overcoming natural disasters and ecological disasters to minimize environmental damage, social impacts, and economic losses. The environmental management model carried out by the Pesantren Al-Khairat in Palu in the coastal area and geographically crossed by the equator, can reduce environmental damage and can be used as a role model in disaster mitigation and eco-implementation implementation.